Improvement in photovoltaic performance of anthracene-containing PPE-PPV polymer-based bulk heterojunction solar cells with silver nanoparticles - Tore, Nesrin; Parlak, Elif Alturk; Tumay, Tulay Asli; Kavak, Pelin; Sarioglan, Serife; Bozar, Sinem; Gunes, Serap; Ulbricht, Christoph; Egbe, Daniel Ayuk Mbi (SPRINGER, 2014)
In this study, we investigated the effect of silver nanoparticles (Ag NPs) in the active layer of anthracene-containing poly(p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene):phenyl-C-61-butyric acid methyl ester (AnE-PVstat:PCBM)-based bulk heterojunction solar cells. By incorporating Ag NPs of 6 nm in diameter, the power conversion efficiency of AnE-PVstat:PCBM solar cells was improved to 3.10 % from a value of 2.46 % for the solar cells fabricated without nanoparticles. Moreover, ISOS-L-1 stability test showed that the lifetime of the cells was also significantly improved by doping Ag NPs into the active layer.
Keywords: Organic solar cells; Silver nanoparticles; PPE-PPVs; Stability test; Energy conversion; ALKOXY SIDE-CHAINS; EFFICIENCY; PHOTODETECTORS; ENHANCEMENT; Chemistry; Science & Technology - Other Topics; Materials Science